Chiral Resolution using Supramolecular‐Templated Mesostructured Materials. Issue 32 (28th June 2019) - Huang, Yanan; Vidal, Xavier; Garcia‐Bennett, Alfonso E.
Abstract: Chiral resolution using non‐functionalized mesoporous particles is demonstrated for a variety of enantiomeric pairs. This is achieved through the use of supramolecular templated silica materials prepared with guanosine monophosphate (NGM‐1) and folic acid (NFM‐1) which enable direct chiral transcription onto the surface of the mesopores after solvent extraction and post calcination of the template. The chiral selectivity and kinetics of the mesoporous materials are measured by circular dichroism (CD) spectroscopy on adsorbed molecules with different affinities for the pore surface. NGM‐1 and NFM‐1 have opposite enantiomeric selectivity for enantiomeric pairs. These results significantly increase the potential of mesoporous materials for chiral separation and enantiomeric catalysis. Abstract : Talkin′ bout a resolution : Supramolecular templates transfer their chirality to porous surfaces resulting in mesoporous silica particles capable of selective adsorption of enantiomers and separation of racemic mixtures.